Artistic – Theoretical Interpretation Of National And Universal Features In The Image Of The Lyric Hero (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article analyzes the national and universal characteristics manifested in the image of the lyric hero from a literary-theoretical perspective. The study illuminates the theoretical foundations of the concept of the lyric hero, its relationship with the author's personality, and its aesthetic nature as an artistic image. It also reveals the role of national cultural traditions, historical memory, and the mentality of the people in the formation of the image of the lyric hero. The author emphasizes that universal human emotional experiences such as love, suffering, hope, and philosophical reflection also occupy an important place in the image of the lyric hero. As a result of analyses conducted on the basis of comparative-analytical, historical-literary, and hermeneutic methods, it is substantiated that the image of the lyric hero represents an artistic-aesthetic phenomenon formed through the harmony of national and universal features. The results of the research demonstrate the necessity of studying the image of the lyric hero on the basis of a complex methodological approach.
Keywords: lyric hero; artistic image; nationality; universality